Characterization of a tubular electrochemical reactor for the degradation of the commercial diuron herbicide. Issue 10 (28th April 2020) - de Matos, Danielle Barbosa; Barbosa, Marcus Paulo Rosa; Leite, Otávio Monteiro; Steter, Juliana Ribeiro; Lima, Nayara Silva; Torres, Nádia Hortense; Marques, Maria Nogueira; de Alsina, Odelsia Leonor Sanchez; Cavalcanti, Eliane Bezerra
ABSTRACT: After designing and constructing an electrochemical reactor with concentric electrodes and tangential feed (RECT), it is necessary to characterize it and to study its performance. The experimental study of the residence time distribution (RTD) was conducted for flow rates of 2.78 × 10 –6  m 3  s –1, 8.33 × 10 –6  m 3  s –1 and 13.9 × 10 –6  m 3  s –1 . According to the values obtained from the Pe number (0.67–1.52), the RECT fits as tubular with great dispersion. The determined empirical correlation (Sh = 18.16 Re 0.50 Sc 0.33 ) showed a laminar flow behavior in the range of Reynolds number (Re) between 23 and 117. In order to use RECT in effluent treatment, an electrochemical oxidation study of the Diuron model molecule (Nortox ® ) was performed to analyze reactor performance in a closed system with total reflux. A decay kinetics of pseudo-first order was associated with the decay of the concentration of diuron and 30% mineralization in 180 min of process were obtained, having a total volume of 4 × 10 –3  m 3 and an initial concentration of commercial Diuron in 215.83 mg dm –3 . Eleven by-products were identified by HPLC–MS analysis and, from this, it was possible to propose a route of degradation of the diuron. From these observations, it can be inferred that the studied electrochemical reactor had applicability in the degradation of recalcitrant compounds, as is the case of commercial diuron. Make some changes in the electrochemical reactor studied and other advanced oxidative processes, such as electro-Fenton, can be associated with the studied system to achieve a better conversion efficiency. GRAPHICAL ABSTRACT: